Commentaires sur le traitement des inventaires dans le modèle CANDIDE - Montmarquette, Claude (L'Actualité économique, 1976)
AbstractThe CANDIDE model referring to the traditional stock adjustment model to specify its inventory investment equations, the comment stresses the difficulty of that kind of model to explain and predict correctly the behaviour of inventory holdings. After pointing out the incredible loan adjustment lags usually associated with the stock adjustment model, and also obtained with CANDIDE, the comment draws the attention on the annual data basis of CANDIDE and the fact that the behaviour of inventory holdings is most likely to be better observed with monthly data. Some references to alternative models of inventory holdings and to the temporal decision problem are also given.